2005
DOI: 10.4103/0019-5545.55960
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of inappropriate ADH secretion (SIADH) associated with citalopram use

Abstract: Selective serotonin reuptake inhibitors (SSRIs) can cause the syndrome of inappropriate antidiuretic hormone secretion (SIADH). SIADH is associated with hyponatraemia without oedema. We report the case of a patient who developed acute-onset hyponatraemia that progressed rapidly to serious neurological dysfunction shortly after the introduction of citalopram. All SSRIs including citalopram should be used with care in the elderly. The water and electrolyte balance should be monitored carefully during SSRI therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…An increase in the number of cases of drug-induced hyponatremia (a condition of abnormally low blood sodium levels below 130 mEq/L) have been reported during the warm seasons in Sweden [ 76 ]. Consumption of the most widely prescribed antidepressants, SSRIs, is known to be associated with inappropriate antidiuretic hormone secretion (SIADH) [ 77 , 78 , 79 ], which is characterized by hyponatremia, either caused by overstimulation of the release of ADH, or by increased renal responsiveness to ADH [ 80 , 81 ]. The mechanism by which SSRIs cause hyponatremia remains unclear, but it has been suggested that, SSRIs, to some degree, affect noradrenaline reuptake.…”
Section: Behavioral State Neurotransmittersmentioning
confidence: 99%
“…An increase in the number of cases of drug-induced hyponatremia (a condition of abnormally low blood sodium levels below 130 mEq/L) have been reported during the warm seasons in Sweden [ 76 ]. Consumption of the most widely prescribed antidepressants, SSRIs, is known to be associated with inappropriate antidiuretic hormone secretion (SIADH) [ 77 , 78 , 79 ], which is characterized by hyponatremia, either caused by overstimulation of the release of ADH, or by increased renal responsiveness to ADH [ 80 , 81 ]. The mechanism by which SSRIs cause hyponatremia remains unclear, but it has been suggested that, SSRIs, to some degree, affect noradrenaline reuptake.…”
Section: Behavioral State Neurotransmittersmentioning
confidence: 99%
“…The incidence of hyponatraemia because of citalopram reported in the literature varies from 0.5% to 32%1 and has been reported to be three times higher than with other antidepressants 2. Most of the other reported cases of hyponatraemia thought to be because of citalopram are associated with milder degrees of hyponatraemia which improved on stopping the drug or with fluid restriction.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the other reported cases of hyponatraemia thought to be because of citalopram are associated with milder degrees of hyponatraemia which improved on stopping the drug or with fluid restriction. Two other cases report hyponatraemia of less than 110 mmol/L 2 3. Hypertonic saline requires caution because of the risk of osmotic demyelination particularly in high-risk groups which include patients with alcoholism, malnutrition, hypokalaemia, burns and elderly women on thiazide diuretics 4.…”
Section: Discussionmentioning
confidence: 99%
“…The hyponatremic effect is attributed to SSRI-induced release of antidiuretic hormone, leading to the SIADH. [ 3 ] SIADH is characterized by a low serum sodium concentration (<135 mmol/L), urinary osmolality exceeding 200 mOsm/kg, a urinary sodium concentration exceeding 20 mmol/L, and serum osmolality of <280 mOsm/kg. [ 5 ] The main modality of management in SIADH is water restriction, although in severe symptomatic cases hypertonic saline (3%) and drugs such as loop diuretics (frusemide), demeclocycline, and vaptans can be used.…”
Section: Discussionmentioning
confidence: 99%
“…This association of hyponatremia due to SSRI has been usually reported in elderly patients (above 60 years age). [ 3 ] To the authors' knowledge, this is the second case being reported in a middle-aged female from the Indian subcontinent, the first being reported by Kar and Sharmaz in 2014. [ 4 ]…”
Section: Introductionmentioning
confidence: 94%